Problem-Based Learning as a Learning Innovation Strategy To Improve the Motivation and Learning Outcomes of Distance Learning - Handini Novita Sari; I Made Arsana; Ika Nurjannah (Universitas Negeri Padang, 2023)
Distance learning, which lasted long during the COVID-19 emergency, has led to student boredom in participating in the learning process. The impact is a decrease in learning outcomes, so innovative learning methods are needed to minimize this. This study will analyze the application of problem-based learning by considering learning outcomes and student motivation. The subjects of this study were 5th-semester Mechanical Engineering students. The design of this study used classroom action using the Kemmis and McTaggart models, which consisted of three steps: planning, acting and observing, reflecting, and carried out in two cycles. The research data was then analyzed quantitatively based on predetermined indicators. Based on this research study, it was found that learning outcomes data increased by 36% from cycle I to cycle II. The results of student learning motivation in Process I were 27.3% had high learning cycles, 63.7% had moderate learning cycles, and 9.9%. In cycle II, students' learning motivation increased from high, medium, and low, respectively, by 45%, 52%, and 3%. Based on the results of the analysis, this means that problem-based learning strategies improve learning outcomes and student learning motivation.